Maxim Application User Satisfaction Analysis Using The User Experience Questionnaire Method - M Rido Rizki; M. Rudi Sanjaya (INOVTEK Polbeng - Seri Informatika, 2024)
This research aimed to explore the user experience of the Maxim application in Palembang City using the User Experience Questionnaire (UEQ) method. As the need for flexible and affordable online transportation increases in big cities, applications like Maxim are becoming people's top choice. Despite having competitive rates, Maxim often gets mixed reviews from users. This study focused on measuring user satisfaction based on UEQ variables, namely attractiveness, efficiency, clarity, reliability, stimulation, and novelty, involving 206 respondents. The outcomes of the research reveal that users generally have a positive experience on aspects of attractiveness, clarity, and efficiency, but the values on novelty, stimulation, and reliability are still low, indicating room for improvement. This outcomes is expected to be a reference for Maxim developers in optimizing the quality of applications to meet the needs of users in Palembang, as well as providing guidance for similar application providers in improving the user experience.